Poverty and Gender in Malawi : A Background Paper for the 2021 Malawi Poverty Assessment - Gross, Melanie; Muller, Miriam; Caruso, German Daniel; Cardona Sosa, Lina Marcela (Washington, DC: World Bank, 2022)
The paper, which serves as a gender background paper for the 2021 Malawi Poverty Assessment, is structured as follows. It first presents the data and empirical strategy. Chapter two presents poverty data and discusses the intersection of poverty and gender. Poverty by household composition is essential for understanding gendered differences in poverty. From there, chapter three explores gender disparities in economic opportunities, following the analytical framework cited earlier. The authors will then move to potential drivers of economic outcomes: endowments (chapter four) and agency (chapter five). The last section offers conclusions.